Crafts for kids who are wild about outer space - Ross, Kathy (Katharine Reynolds), 1948- (Millbrook Press, 1997)
Provides instructions for twenty projects, creating such things as a planet mobile, constellation tack board, space helmet, moon buggy, pop-up alien puppet, and rocket pin.